2020
DOI: 10.4014/jmb.2007.07005
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Miniaturized Culture Screening for Cellulolytic Fungi and Their Agricultural Lignocellulosic Degradation

Abstract: The substantial use of fungal enzymes to degrade lignocellulosic plant biomass has widely been attributed to the extensive requirement of powerful enzyme-producing fungal strains. In this study, a two-step screening procedure for finding cellulolytic fungi, involving a miniaturized culture method with shake-flask fermentation, was proposed and demonstrated. We isolated 297 fungal strains from several cellulose-containing samples found in two different locations in Thailand. By using this screening strategy, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 59 publications
0
2
0
1
Order By: Relevance
“…Bahan pakan yang bersifat padat dengan kadar air sedikit mendukung terbentuknya kondisi mirkroaerofilik selama fermentasi sehingga terbentuk kondisi fermentasi dengan ketersediaan oksigen dalam jumlah terbatas yang diperlukan oleh jamur selulolitik untuk mendegradasi bahan yang tinggi selulosa selama proses fermentasi. Jamur selulolitik berpotensi dalam degradasi lignoselulosa pada bahan ditunjukkan dengan adanya biokonversi lignoselulosa menjadi glukosa (Arnthong et al, 2020). Jamur selulolitik mendegradasi selulosa untuk digunakan sebagai sumber karbon untuk pertumbuhan, metabolisme, dan pengaturan ekspresi gen (Hu et al, 2020).…”
Section: Pembahasanunclassified
“…Bahan pakan yang bersifat padat dengan kadar air sedikit mendukung terbentuknya kondisi mirkroaerofilik selama fermentasi sehingga terbentuk kondisi fermentasi dengan ketersediaan oksigen dalam jumlah terbatas yang diperlukan oleh jamur selulolitik untuk mendegradasi bahan yang tinggi selulosa selama proses fermentasi. Jamur selulolitik berpotensi dalam degradasi lignoselulosa pada bahan ditunjukkan dengan adanya biokonversi lignoselulosa menjadi glukosa (Arnthong et al, 2020). Jamur selulolitik mendegradasi selulosa untuk digunakan sebagai sumber karbon untuk pertumbuhan, metabolisme, dan pengaturan ekspresi gen (Hu et al, 2020).…”
Section: Pembahasanunclassified
“…Additionally, through the use of specific assay conditions or detection methods, the target enzymes can be identified with better specificity and sensitivity compared to agar plate screening methods. Moreover, screening in liquid media also mimics industrial submerged culture conditions, thus allowing the identification of potential microbes and enzymes for industrial applications [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they are considered as potential alternatives to the industrial cellulase-producer Trichoderma reesei [ 18 , 19 ]. Penicillium oxalicum strains are commonly isolated from the natural environment for their high cellulase-producing capacities [ 20 , 21 ]. Genomic and proteomic analyses of a P. oxalicum wild-type strain 114-2 have revealed that it produces a lignocellulolytic enzyme system rich in hemicellulases [ 22 ].…”
Section: Introductionmentioning
confidence: 99%